Production of Biocoal from Wastewater Sludge and Sugarcane Bagasse: A Review - Zinhle Mkhwanazi; Yusuf Makarfi Isa; Shadana. T. Vallabh (Atmosphere, 2023)
The rising volume of wastewater sludge and sugarcane bagasse is becoming a prominent concern globally. Furthermore, the growing demand for fuel coupled with the depletion of fossil fuel reserves in South Africa demonstrates the need for alternative energy sources. To minimize the reliance on fossil-based energy sources, a renewable resource such as biomass can be optimized as an energy source. Wastewater sludge and bagasse have the energy potential to produce high-calorific-value biocoal; this will contribute to the supply of energy in South Africa. The synthesis of biocoal from wastewater sludge and bagasse through an artificial synthetic coal production process, i.e., hydrothermal carbonization (HTC), is preferred over other thermal conversion techniques as HTC is capable of handling feed having a high (75–90%) moisture content. This article focuses on the production of biocoal from wastewater sludge and sugarcane bagasse as an alternative to sustainable bioenergy supply and as one of the potential solutions for reducing net CO2 greenhouse gas (GHG) emissions from fossil-fuel power plants, and addresses the use of different thermochemical technologies, previous studies on the composition of wastewater sludge and bagasse, and the benefits of hydrothermal carbonization.